Kinetic studies on the reaction of NO with iron(ii) complexes using low temperature stopped-flow techniques. Issue 27 (1st July 2020) - Specht, Pascal; Oßberger, Martin; Klüfers, Peter; Schindler, Siegfried
Abstract : Quite different reaction mechanisms were observed in a kinetic study of NO binding to iron(ii ) complexes. Abstract : Low temperature stopped-flow techniques were used to investigate the reaction of three different iron(ii ) complexes with nitrogen monoxide. The kinetic studies allowed calculation of the activation parameters from the corresponding Eyring plots for all three systems. The reaction of iron(ii ) chloride with NO leading to the formation of MNIC (mononitrosyl-iron-complex) and DNIC (dinitrosyl-iron-complex) led to activation parameters of Δ H ‡ = 55.4 ± 0.4 kJ mol −1 and Δ S ‡ = 13 ± 2 J K −1 mol −1 for MNIC and Δ H ‡ = 32 ± 6 kJ mol −1 and Δ S ‡ = −193 ± 21 J K −1 mol −1 for DNIC . Formation of MNIC turned out to be much faster in comparison with DNIC . In contrast, activation parameters for the formation of monoculear [Fe(bztpen)(NO)](OTf)2 (bztpen = N -benzyl- N, N ′, N ′-tris(2-pyridylmethyl)-ethylenediamine) Δ H ‡ = 17.8 ± 0.8 kJ mol −1 and Δ S ‡ = −181 ± 3 J K −1 mol −1 supported an associative mechanism. Interestingly, [Fe(bztpen)(CH3 CN)](OTf)2 does not react with dioxygen at all. Furthermore, activation parameters of Δ H ‡ = 37.7 ± 0.7 kJ mol −1 and Δ S ‡ = −66 ± 3 J K −1 mol −1 were obtained for the reaction of NO with the dinuclear iron(ii ) H-HPTB complex (H-HPTB = N, N, N ′, N ′-tetrakis(2-benzimidazolylmethyl)-2-hydroxy-1, 3-diaminopropane), [Fe2 (H-HPTB)(Cl)3 ]. The kinetic data allowed postulation of the mechanisms for all of these reactions.